2017
DOI: 10.1007/s13592-017-0512-8
|View full text |Cite
|
Sign up to set email alerts
|

Internal hive temperature as a means of monitoring honey bee colony health in a migratory beekeeping operation before and during winter

Abstract: -Internal temperatures of honey bee hives kept at different sites in North Dakota were monitored before and during winter to evaluate the effects of treatment, in the form of exposure to commercial pollination, and location on colony health. In October, hives exposed to commercial pollination during the summer had fewer adult bees and less brood than hives kept near natural forage, as well as lower average temperatures throughout winter. Within-day temperature variability was higher among hives exposed to comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 28 publications
(35 reference statements)
7
53
2
1
Order By: Relevance
“…However, our F2 temperature results suggest that effects of neonicotinoids on individual bees may not scale up to cause colony-level dysfunction. The lack of a treatment effect on temperature regulation in our study contrasts with Colin et al (2019) [33], who demonstrated that colonies chronically exposed to 5 ng/g of the neonicotinoid imidacloprid through sugar syrup had higher average overwinter in-hive temperatures and decreased colony temperature variability, and Meikle et al (2017) [34] who observed that a history of commercial pollination activity and agrochemical exposure was associated with lower overwinter internal colony temperatures and increased colony temperature variability. These inconsistent results regarding the effect of pesticide exposure on colony temperature regulation may be explained by variation in overwintering climate and beekeeping practices.…”
Section: Effects Of Thiamethoxam On Overwintering Colonies Of Apis Mecontrasting
confidence: 98%
“…However, our F2 temperature results suggest that effects of neonicotinoids on individual bees may not scale up to cause colony-level dysfunction. The lack of a treatment effect on temperature regulation in our study contrasts with Colin et al (2019) [33], who demonstrated that colonies chronically exposed to 5 ng/g of the neonicotinoid imidacloprid through sugar syrup had higher average overwinter in-hive temperatures and decreased colony temperature variability, and Meikle et al (2017) [34] who observed that a history of commercial pollination activity and agrochemical exposure was associated with lower overwinter internal colony temperatures and increased colony temperature variability. These inconsistent results regarding the effect of pesticide exposure on colony temperature regulation may be explained by variation in overwintering climate and beekeeping practices.…”
Section: Effects Of Thiamethoxam On Overwintering Colonies Of Apis Mecontrasting
confidence: 98%
“…Temperature control by honey bees is crucial for brood rearing (Stabentheiner et al 2010) and some degree of temperature control is evident among groups of bees even in the absence of brood (Meikle et al 2017). Maintaining the cluster temperature is a metabolically expensive activity of the colony for much of the year (Gates 1914;Milner 1921).…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the cluster temperature is a metabolically expensive activity of the colony for much of the year (Gates 1914;Milner 1921). Internal hive temperature over time has been linked to changes in colony size and phenology (Meikle et al 2016b(Meikle et al , 2017 and thus can be a useful variable to monitor hive status. In a Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…The area of sealed brood per frame was estimated later from the frame photographs using either ImageJ software (version 1.47. W. Rasband, National Institutes of Health, USA), or CombCount; 38 this method has been described in other publications (see 8,13,16,25 ). Any colony that had capped brood was included in the study.…”
Section: Methodsmentioning
confidence: 99%